Incidental detection of germline variants of potential clinical significance by massively parallel sequencing in haematological malignancies. Issue 1 (11th August 2017) - Yannakou, Costas K; Jones, Kate; Ryland, Georgina L; Thompson, Ella R; Reid, Gareth; McBean, Michelle; Trainer, Alison; Westerman, David; Blombery, Piers
Abstract : Massively parallel sequencing (MPS) technology has become routinely available for diagnosis, prognostication and therapeutic decision-making in haematological malignancies. However, increased throughput and wider coverage of genes can have unintended consequences. Germline variants of potential clinical significance (GVPCSs) detected during cancer testing may have implications for patients and families beyond the biological evaluation of a specific tumour. 721 reports generated from MPS panels used in the routine testing of myeloid and lymphoid malignancies were reviewed and variants within genes of potential germline relevance ( TP53, RUNX1, GATA2 and WT1 in all contexts and CBL, KRAS and NRAS in the setting of juvenile myelomonocytic leukaemia) were analysed. A variant allele fraction threshold of ≥33.09% for considering germline origin of variants within cancer samples was established. The detection rate of incidental, pathogenic germline variants was 0.42%. Patient education and confirmatory germline sample testing of GVPCSs in appropriate circumstances are recommended.